TINJAUAN OBAT ANTIKEJANG DALAM PENATALAKSANAAN KEJANG DEMAM: ASPEK FARMAKOLOGIS, STRUKTUR KIMIA DAN PENDEKATAN KLINIS - Fauziah Hasdin (JURNAL PHARMA BHAKTA, 2025)
Background: Febrile seizures are the most common neurological disorder in children aged 6 months to 6 years. Although generally benign, complex febrile seizures are associated with increased risk of epilepsy. Objective: This review analyzes anticonvulsant drugs used in febrile seizure management, emphasizing the correlation between chemical structure, pharmacokinetics, and clinical efficacy, while assessing the potential of emerging agents. Method: A narrative review was conducted using literature published between 2010 and 2025, retrieved from PubMed, ScienceDirect, and Google Scholar, with keywords related to anticonvulsants and febrile seizures.Result: Benzodiazepines demonstrate rapid onset and effectiveness in acute management due to their lipophilic structure. Prophylactic agents such as phenobarbital and valproate are effective but linked to long-term adverse effects. Newer agents like levetiracetam and lacosamide offer favorable pharmacokinetics, low toxicity, and selective non-GABAergic mechanisms. Conclusions: Anticonvulsant selection should be guided by chemical structure and pharmacokinetic profile. Benzodiazepines remain first-line treatment, while levetiracetam and lacosamide are promising options for complex cases. Further research is needed to strengthen clinical evidence in pediatric populations.